Transformation Groups Applied to Two-Dimensional Boundary Value Problems in Fluid Mechanics - Pereira, Kevin Paul (Journal of nonlinear mathematical physics, 2008)
The boundary value problems for the two-dimensional, steady, irrotational flow of a frictionless, incompressible fluid past a wedge and a circular cylinder are considered. It is shown that by considering first the invariance of the boundary condition we are able to obtain a transformation group that can be used to solve each boundary value problem.